Preeclampsia is Associated With Reduced ISG15 Levels Impairing Extravillous Trophoblast Invasion - Asli Ozmen; Ozlem Guzeloglu-Kayisli; Selcuk Tabak; Xiaofang Guo; Nihan Semerci; Chinedu Nwabuobi; Kellie Larsen; Ali Wells; Asli Uyar; Sefa Arlier; Ishani Wickramage; Hasan Alhasan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Among several interleukin (IL)-6 family members, only IL-6 and IL-11 require a gp130 protein homodimer for intracellular signaling due to lack of intracellular signaling domain in the IL-6 receptor (IL-6R) and IL-11R. We previously reported enhanced decidual IL-6 and IL-11 levels at the maternal-fetal interface with significantly higher peri-membranous IL-6 immunostaining in adjacent interstitial trophoblasts in preeclampsia (PE) vs. gestational age (GA)-matched controls. This led us to hypothesize that competitive binding of these cytokines to the gp130 impairs extravillous trophoblast (EVT) differentiation, proliferation and/or invasion. Using global microarray analysis, the current study identified inhibition of interferon-stimulated gene 15 (ISG15) as the only gene affected by both IL-6 plus IL-11 vs. control or IL-6 or IL-11 treatment of primary human cytotrophoblast cultures. ISG15 immunostaining was specific to EVTs among other trophoblast types in the first and third trimester placental specimens, and significantly lower ISG15 levels were observed in EVT from PE vs. GA-matched control placentae (p = 0.006). Induction of primary trophoblastic stem cell cultures toward EVT linage increased ISG15 mRNA levels by 7.8-fold (p = 0.004). ISG15 silencing in HTR8/SVneo cultures, a first trimester EVT cell line, inhibited invasion, proliferation, expression of ITGB1 (a cell migration receptor) and filamentous actin while increasing expression of ITGB4 (a receptor for hemi-desmosomal adhesion). Moreover, ISG15 silencing further enhanced levels of IL-1β-induced pro-inflammatory cytokines (CXCL8, IL-6 and CCL2) in HTR8/SVneo cells. Collectively, these results indicate that ISG15 acts as a critical regulator of EVT morphology and function and that diminished ISG15 expression is associated with PE, potentially mediating reduced interstitial trophoblast invasion and enhancing local inflammation at the maternal-fetal interface. Thus, agents inducing ISG15 expression may provide a novel therapeutic approach in PE.